(untitled) (Élisée - Revista de Geografia da UEG, 2024)
This article aims, as from on a bibliographical review about some works by Milton Santos, to present and discuss about of epistemological elements, categories of analysis and dialectical pairs important for the understanding of space and territory in the work of this Brazilian geographer. From the material selected it was possible to verify that Milton Santos, throughout his academic and intellectual trajectory, provided Geography with an important theoretical and methodological basis, mainly for the understanding of the reality of the countries of the Southern Hemisphere.